Efectos del crédito hipotecario sobre el precio de la vivienda nueva NO VIS en Medellín (2018)
Exploring the credit factors in new housing NO VIS, allows different views of social dynamics that facilitate access or not to it. In this sense, determine the effects of the mortgage loan on the price of new non-VIS housing in the city of Medellin for the period between 2009, and the first half of 2017; beyond allowing us to show that these variables are inversely related, it allows us to identify other economic factors relevant to this study. The methodology used for this research was based on the supply and demand functions, in order to establish the relationship between the mortgage rate and the price per square meter for new housing NO VIS. Using an autoregressive moving average model and three-stage least squares model, it is evident that the variable with the greatest impact on housing prices is the Mortgage Rate, presenting a negative relationship for both the supply and demand functions.